2007
DOI: 10.1183/09031936.00064006
|View full text |Cite
|
Sign up to set email alerts
|

Airway resistance variability and response to bronchodilator in children with asthma

Abstract: Variability of airway function is a feature of asthma, spanning timescales from months to seconds. Short-term variation in airway resistance (Rrs) is elevated in asthma and is thought to be due to increased variation in the contractile activation of airway smooth muscle. If true, then variation in Rrs should decrease in response to bronchodilators, but this has not been investigated.Using the forced oscillation technique, Rrs and the variation in Rrs from 4-34 Hz were measured in 39 children with well-controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 46 publications
8
44
2
Order By: Relevance
“…Using end-inspiratory values may theoretically decrease the contribution of flow to RRSi, yet, transition from RRSi to RRSe would have to be smooth enough to accurately identify undistorted near zero flow values (14). That the ⌬RRS DI could not be recovered in a significant proportion of subjects may induce a bias in interpreting the case-control difference, for instance, expressing the fact that asthmatic children may show lower RRS repeatability (41), but the overall proportion of data rejected was very similar in asthma and controls. Moreover, it may be argued that some sensitization of the ⌬RRS DI might have resulted from taking a through instead of mean RRSi after the DI, but the difference between asthma and control was significant after exercise and not at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Using end-inspiratory values may theoretically decrease the contribution of flow to RRSi, yet, transition from RRSi to RRSe would have to be smooth enough to accurately identify undistorted near zero flow values (14). That the ⌬RRS DI could not be recovered in a significant proportion of subjects may induce a bias in interpreting the case-control difference, for instance, expressing the fact that asthmatic children may show lower RRS repeatability (41), but the overall proportion of data rejected was very similar in asthma and controls. Moreover, it may be argued that some sensitization of the ⌬RRS DI might have resulted from taking a through instead of mean RRSi after the DI, but the difference between asthma and control was significant after exercise and not at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…This is a useful tool in evaluating lung function in young children with limited ability to cooperate 1 and older children. [2][3][4] FOT has been shown to be applicable in the clinical evaluation of preschool children with cystic fibrosis 5 as well as older children with cystic fibrosis during a respiratory tract exacerbation. 6 Lung function measured with FOT has also been evaluated in children born prematurely with or without neonatal chronic lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] FOT has also been shown to be a valid tool in the assessment of bronchodilator response (BDR) in different populations of patients, especially asthmatic or wheezing children. 4,[10][11][12][13][14] Before FOT can be introduced into clinical practice as a routine test, appropriate reference values from healthy populations are needed. Although, a number of data sets from children have been published these are likely to be specific to the equipment used and to the study population.…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, Que and colleagues demonstrated that respiratory system resistance measured by FOT was more variable in patients with asthma than in healthy control subjects, even across time spans as short as 15 minutes (66). This variability has subsequently been demonstrated in a number of other studies involving both adults and children (22,(67)(68)(69). One study has even suggested that home monitoring of FOT for just 2 minutes a day over only 8 days could yield sufficient information to calculate a conditional probability of lung function deterioration over the subsequent week (70).…”
Section: More Sensitive Lung Function Measures?mentioning
confidence: 98%